Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How would you evaluate the following series?

$$\lim_{n\to\infty} \sum_{k=1}^{n^2} \frac{n}{n^2+k^2} $$


share|cite|improve this question
Maple says $\pi/2$ – i. m. soloveichik Sep 4 '12 at 14:20
It looks like you might be able to interpret the summand as a Riemann sum ... – Michael Joyce Sep 4 '12 at 14:31
@ Michael Joyce: Yeah. That's true. Anyway, I'm interested in more approaching ways if possible. – user 1618033 Sep 4 '12 at 14:31
up vote 29 down vote accepted

Recall that for any decreasing function $f:\mathbb{R}\to\mathbb{R}$ and any $N>1$ we have $$ \int\limits_1^{N+1}f(x)dx\leq \sum\limits_{k=1}^{N}f(k)\leq \int\limits_0^N f(x)dx $$ After substitutions $N=n^2$, $f(x)=n/(n^2+x^2)$ and simple computations we have $$ \arctan\frac{n^2+1}{n}-\arctan \frac{1}{n}\leq\sum\limits_{k=1}^{n^2}\frac{n}{n^2+k^2}\leq\arctan n $$ Lets take a limit $n\to\infty$, then from sandwich lemma it follows $$ \lim\limits_{n\to\infty}\sum\limits_{k=1}^{n^2}\frac{n}{n^2+k^2}=\frac{\pi}{2} $$

P.S. First solution was not rigor enough.

share|cite|improve this answer
How is the decreasing function property called? – REr Nov 11 '14 at 17:51
@REr, decreasing – Norbert Nov 11 '14 at 18:46

Hint: $$\int_0^a f(x) dx \approx \sum_{k=0}^{na} \frac{1}{n}f\left(\frac{k}{n}\right)$$ Use $f(x) = \frac{1}{1+x^2}$.

Addendum: Fortunately, $f(x)$ is strictly decreasing, therefore the error is bounded by $\frac{f(0)-f(a)}n$, which again is $<\frac1n$, independent of $a$. This last observation allows us to use $a=n$ without spoiling convergence to $\int_0^\infty f(x) dx$.

share|cite|improve this answer
With $a=n$, the approach becomes unconventional and seems to require some further analysis. – Did Sep 4 '12 at 17:42
@did: I believe you're right. I've tried to add the necessary analysis to my answer. – robjohn Sep 5 '12 at 12:46

Using $x=k/n$ and $\mathrm{d}x=1/n$ $$ S_m(n)=\sum_{k=0}^{mn}\frac{n}{n^2+k^2}=\sum_{k=0}^{mn}\frac{1}{1+(k/n)^2}\frac1{\vphantom{k^2}n}\tag{1} $$ is a Riemann Sum for $$ I_m=\int_0^m\frac{\mathrm{d}x}{1+x^2}\tag{2} $$ For any $m$ and $n$, we have $$ \sum_{k>mn}\frac{n}{n^2+k^2}\le\sum_{k>mn}\frac{n}{k(k-1)}=\frac1m\tag{3} $$ which implies that $$ S_m(n)\le S_\infty(n)=\lim_{m\to\infty}S_m(n)\le S_m(n)+\frac1m\tag{4} $$ Since $$ I_\infty=\lim\limits_{m\to\infty}I_m=\int_0^\infty\frac{\mathrm{d}x}{1+x^2}\tag{5} $$ for any $\epsilon>0$, there is an $m_\epsilon\ge\frac1{\large\epsilon}$ so that for $m\ge m_\epsilon$, $$ I_\infty-\epsilon\le I_m=\lim_{n\to\infty}S_m(n)\le I_\infty\tag{6} $$ Finally, there is an $n_\epsilon\ge m_\epsilon$ so that for $n\ge n_\epsilon$, $$ I_\infty-2\epsilon\le S_{m_\epsilon}(n)\le I_\infty+\epsilon\tag{7} $$ Since $m_\epsilon\ge\frac1{\large\epsilon}$, $(4)$ and $(7)$ yield that for $n\ge n_\epsilon$ $$ I_\infty-3\epsilon\le S_n(n)\le I_\infty+2\epsilon\tag{8} $$ Since $\epsilon$ was arbitrary, we get that $$ \lim_{n\to\infty}S_n(n)=I_\infty\tag{9} $$ which translates to $$ \lim_{n\to\infty}\sum_{k=0}^{n^2}\frac{n}{n^2+k^2}=\int_0^\infty\frac{\mathrm{d}x}{1+x^2}=\frac\pi2\tag{10} $$

share|cite|improve this answer
Nice and detailed (+1) – user 1618033 Sep 5 '12 at 12:54
@Chris'sister: This looks deceptively like a reference to Riemann Sums, but since the upper index is $n^2$, we have to handle the improper integral carefully. – robjohn Sep 5 '12 at 13:01
@ robjohn: Right. And this is because m is not fixed, but it tends to $\infty$. – user 1618033 Sep 5 '12 at 13:03

Here's another approach.

First, note that $$\begin{eqnarray*} \sum_{k=n^2+1}^\infty \frac{n}{n^2+k^2} &<& \sum_{k=n^2+1}^\infty \frac{n}{k^2} \\ &\le& n\int_{n^2}^\infty \frac{dx}{x^2} \\ &=& \frac{1}{n}. \end{eqnarray*}$$ We also need the partial fraction expansion of $\coth x$, $$\begin{eqnarray*} \coth x &=& \lim_{N\to\infty} \sum_{k=-N}^N \frac{1}{x-i k \pi} \\ &=& \frac{1}{x} + \sum_{k=1}^\infty \frac{2x}{x^2+k^2\pi^2}. \end{eqnarray*}$$ Then we find $$\begin{eqnarray*} \lim_{n\to\infty} \sum_{k=1}^{n^2} \frac{n}{n^2+k^2} &=& \lim_{n\to\infty}\left( \sum_{k=1}^\infty \frac{n}{n^2+k^2} - \sum_{k=n^2+1}^\infty \frac{n}{n^2+k^2} \right) \\ &=& \lim_{n\to\infty} \sum_{k=1}^\infty \frac{n}{n^2+k^2} \\ &=& \lim_{n\to\infty} \left(\frac{\pi}{2}\coth n\pi - \frac{1}{2n}\right) \\ &=& \frac{\pi}{2}. \end{eqnarray*}$$

share|cite|improve this answer
@Chris'sister: Sometimes life gets in the way! Aigner and Ziegler have a nice derivation of the partial fraction expansion for $\cot x$ in Proofs from The Book (see Cotangent and the Herglotz trick). I tend to think of such sums in terms of complex analysis. – user26872 Sep 6 '12 at 16:43
yeah, nice! Thanks for the link. – user 1618033 Sep 6 '12 at 17:00

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ $\ds{\lim_{n \to \infty}\sum_{k = 1}^{n^{2}}{n \over n^{2} + k^{2}}:\ {\large ?}}$

\begin{align} \color{#c00000}{\sum_{k = 1}^{n^{2}}{n \over n^{2} + k^{2}}}&= -\Im\sum_{k = 1}^{n^{2}}{1 \over k + \ic n} =-\Im\sum_{k = 0}^{n^{2} - 1}{1 \over k + 1 + \ic n} \\[3mm]&=-\Im\sum_{k = 0}^{\infty}\pars{% {1 \over k + 1 + \ic n} - {1 \over k + n^{2} + 1 + \ic n}} \\[3mm]&=-n^{2}\,\Im\sum_{k = 0}^{\infty} {1 \over \pars{k + n^{2} + 1 + \ic n}\pars{k + 1 + \ic n}} \\[3mm]&=\color{#c00000}{% \Im\bracks{\Psi\pars{1 + \ic n} - \Psi\pars{n^{2} + 1 + \ic n}}} \end{align} where $\ds{\Psi\pars{z}}$ is the Digamma Function. $\ds{z \in {\mathbb C}\verb=\=\braces{0,-1,-2,\ldots}}$. We'll use the property $\ds{\Psi\pars{z} \approx \ln\pars{z}}$ when $\ds{\verts{z} \gg 1}$ and $\ds{\verts{{\rm Arg}\pars{z}} < \pi}$.

Then, \begin{align}\color{#00f}{\large% \lim_{n \to \infty}\sum_{k = 1}^{n^{2}}{n \over n^{2} + k^{2}}}&= \lim_{n \to \infty}\Im\bracks{\Psi\pars{1 + \ic n} - \Psi\pars{n^{2} + 1 + \ic n}} \\[3mm]&=\lim_{n \to \infty} \Im\bracks{\ln\pars{1 + \ic n} - \ln\pars{n^{2} + 1 + \ic n}} \\[3mm]&= \lim_{n \to \infty}\bracks{\arctan\pars{n} - \arctan\pars{n \over n^{2} + 1}} =\color{#00f}{\large{\pi \over 2}} \end{align}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.